Androgen induction of ornithine decarboxylase mRNA in mouse kidney as studied by complementary DNA. - Kontula, K K (1984)
To investigate the mechanisms by which androgens regulate ornithine decarboxylase (OrnDCase; L-ornithine carboxy-lyase, EC 4.1.1.17) in mouse kidney, a cDNA clone encoding OrnDCase mRNA was prepared. Purification of OrnDCase mRNA from kidneys of androgen-treated mice was accomplished by immunoadsorption of renal polysomes to a protein A-Sepharose column and enrichment for poly(A)-containing RNA by oligo(dT)-cellulose. Double-stranded cDNA synthesized from this mRNA was inserted into the Pst I site of plasmid pBR322 by using oligo(dG . dC)-tailing and was propagated in Escherichia coli. Plasmids containing cDNA sequences coding for OrnDCase were identified by differential colony hybridization, by radioimmunological detection of OrnDCase-like antigens in bacterial cultures, and by cell-free translation of hybrid-selected mRNA followed by immunoprecipitation with monospecific OrnDCase antiserum. A restriction endonuclease fragment of the selected plasmid DNA (pODC54) was labeled by nick-translation and used to study changes in OrnDCase mRNA concentration. After a single dose of testosterone, renal OrnDCase mRNA concentration increased as soon as 6 hr and peaked 24 hr after steroid injection, as measured by RNA blot hybridization. Continuous androgen treatment for 4 days resulted in a 10- to 20-fold increase in OrnDCase mRNA concentration in normal animals, but no induction of this mRNA was detected in mice that have an inherent defect of the androgen receptor (testicular feminization). These results indicate that androgens regulate OrnD-Case synthesis in mouse kidney, at least in part, by increasing OrnDCase mRNA accumulation.